The Effect of Local Original Revenue, General Allocation Fund and Special Allocation Fund on Capital Expenditure (Empirical Study on Provinces throughout Indonesia for the 2017 – 2020 Period) - Nuralfiyah Yunianti Dewi; Wieta Chairunesia (Proceeding International Annual Conference Economics, Management, Business, and Accounting, 2023)
This study aims to determine how Regional Original Revenue (PAD), General Allocation Fund (DAU) and Special Allocation Fund (DAK) affect Capital Expenditure (BM) with data from all Indonesian provinces over a period of 3 years (2017-2020). The calculation results of the T statistical test obtained a significance value for Regional Original Revenue of 0.00, General Allocation Fund of 0.00, and Special Allocation Fund of 0.829 so that Regional Original Revenue, General Allocation Fund is positive and significant while Special Allocation Fund is positive and insignificant.